2011
DOI: 10.5798/diclemedj.0921.2011.02.0003
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and other acute phase reactants in patients with chronic obstructive pulmonary disease exacerbation

Abstract: The aim of this study was to investigate the correlation between procalcitonin and other acute phase reactants, and also analyze their relationship with clinical situation in chronic obstructive pulmonary disease (COPD) acute exacerbations. Materials and methods: The study was made with 122 acute COPD exacerbated patients, who were admitted to emergency service. Patients with below 0.25 ng/ml PCT value included Group 1, and the patients with PCT values ≥ 0.25 ng/ml Group 2. Serum procalcitonin levels, erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Chang et al stated that there was no relationship between the WBC count and exacerbation period [8]. Civelek et al reported that the increase in the WBC count during the exacerbation period was not statistically significant [11]. In our study, there was no significant difference in the WBC count between patients in the exacerbation period and those in the stable period.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Chang et al stated that there was no relationship between the WBC count and exacerbation period [8]. Civelek et al reported that the increase in the WBC count during the exacerbation period was not statistically significant [11]. In our study, there was no significant difference in the WBC count between patients in the exacerbation period and those in the stable period.…”
Section: Discussioncontrasting
confidence: 57%
“…Literature review revealed that several laboratory parameters (CRP, PCT, nitric oxide, galectin-3, L-arginine, changes in leukocyte count or formula, etc.) have been investigated in order to distinguish the exacerbation and stable periods of COPD [8][9][10][11][12][13][14]. However, there are only few studies investigating the relationship between PRG4 and COPD, and the results show that PRG4 levels increase in patients with COPD [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation